Search and Retirement under Asymmetric Information - Sheng Bi; François Langot (Institute for the Study of Labor (IZA), 2014)
We consider a labor market where the competitive search equilibrium is inefficient due to asymmetrical information. At the time when firms commit to specific hiring costs, workers hold private information on their intention of entering into retirement before the termination of the contract. When retirement is an event which occurs exogenously and information is complete, the long term employment relationship is preferred by the risk adverse workers. This implies that firms must implement a screening process when the information is asymmetric. We show that the optimal separating contract (an ascending wage profile) distorts the allocation of the workers who will retire later (the 'good' workers) in order to prevent the workers who will retire early (the 'bad' workers) from applying for these jobs. Secondly, we endogenize the retirement decision by considering two cases: an ex ante or ex post heterogeneity. In these two cases, we show that a separating equilibrium always exists, whereby good workers accept an ascending wage profile in order to make themselves differentiate from the 'bad' workers. These asymmetries in the information lead to an excess of retirement compared to the full information economy. Finally, in the case of ex post heterogeneity, we are able to show that the employment rate is unambiguously lower.
Keywords: D82; D86; J14; J26; J64; 330; competitive search equilibrium; separating equilibrium; retirement